2014
DOI: 10.1080/02791072.2013.873843
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptom Reports of Patients Evaluated for the New Mexico Medical Cannabis Program

Abstract: Cannabis is associated with reductions in PTSD symptoms in some patients, and prospective, placebo-controlled study is needed to determine efficacy of cannabis and its constituents in treating PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 13 publications
1
95
0
1
Order By: Relevance
“…As THC acutely induces anxiety, this pattern may also be evident for chronic anxiety symptoms. Two studies were identified, including an uncontrolled retrospective study in civilian patients with PTSD patients [120], and a case study in a patient with severe sexual abuse-related PTSD [121], which showed that chronic cannabis use significantly reduces PTSD symptoms; however, these studies did not include data on the THC:CBD ratio. Thus, overall, no outcome data are currently available regarding the chronic effects of CBD in the treatment of anxiety symptoms, nor do any data exist regarding the potential protective effects of CBD on anxiety potentially induced by chronic THC use.…”
Section: Evidence From Epidemiological and Chronic Studiesmentioning
confidence: 99%
“…As THC acutely induces anxiety, this pattern may also be evident for chronic anxiety symptoms. Two studies were identified, including an uncontrolled retrospective study in civilian patients with PTSD patients [120], and a case study in a patient with severe sexual abuse-related PTSD [121], which showed that chronic cannabis use significantly reduces PTSD symptoms; however, these studies did not include data on the THC:CBD ratio. Thus, overall, no outcome data are currently available regarding the chronic effects of CBD in the treatment of anxiety symptoms, nor do any data exist regarding the potential protective effects of CBD on anxiety potentially induced by chronic THC use.…”
Section: Evidence From Epidemiological and Chronic Studiesmentioning
confidence: 99%
“…A retrospective study of PTSD symptoms in the first 80 people to obtain medical cannabis for PTSD in New Mexico suggested that self-reported symptoms were lower when smoking cannabis (Greer et al, 2014). However, inclusion criteria for this study included self-report of 'significant relief of several major PTSD symptoms when using cannabis.'…”
Section: Eden Evins: Ptsdmentioning
confidence: 99%
“…16,17 There is also some evidence to suggest that smoking cannabis (marijuana is associated with reduced PTSD symptoms). 18 Unfor- tunately, there are still some patients with PTSD who do not respond to initial drug treatment and so other pharmacological agents are suggested. These include antipsychotics, antiadrenergic drugs, and anxiolytics that have demonstrated some efficacy in treating PTSD.…”
mentioning
confidence: 99%
“…These include antipsychotics, antiadrenergic drugs, and anxiolytics that have demonstrated some efficacy in treating PTSD. 18,19 Is there a treatment currently available that could provide benefits and relieve the symptoms of PTSD without the extensive side effects often experienced with medications or length of time with CBT? As Shively et al determined blast exposure cases showed damage to brain structures that could possibly explain the persistent clinical symptoms of patients with blast TBI 1 that has been termed an invisible wound.…”
mentioning
confidence: 99%